2018
DOI: 10.1080/2162402x.2018.1548243
|View full text |Cite
|
Sign up to set email alerts
|

CIITA-related block of HLA class II expression, upregulation of HLA class I, and heterogeneous expression of immune checkpoints in hepatocarcinomas: implications for new therapeutic approaches

Abstract: Forlani (2019) CIITA-related block of HLA class II expression, upregulation of HLA class I, and heterogeneous expression of immune checkpoints in hepatocarcinomas: implications for new therapeutic approaches, OncoImmunology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…Studies have confirmed that some genes can affect HCC due to their occurrence, development, and immune regulation abilities. For example, Elise (Ramia et al, 2019) found that, in HCC cell lines, human leukocyte antigen (HLA) class II expression shortage was caused by the lack of the HLA class II transactivator (i.e., CIITA), and interferon-gamma treatment could not improve the situation. Lee et al (2014) found that CD47(+) HCC cells secreted cathepsin S (CTSS) preferentially using the CTSS/protease-activated receptor 2 (PAR2) loop to regulate liver TICs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that some genes can affect HCC due to their occurrence, development, and immune regulation abilities. For example, Elise (Ramia et al, 2019) found that, in HCC cell lines, human leukocyte antigen (HLA) class II expression shortage was caused by the lack of the HLA class II transactivator (i.e., CIITA), and interferon-gamma treatment could not improve the situation. Lee et al (2014) found that CD47(+) HCC cells secreted cathepsin S (CTSS) preferentially using the CTSS/protease-activated receptor 2 (PAR2) loop to regulate liver TICs.…”
Section: Discussionmentioning
confidence: 99%
“…The first important observation was related to the expression of MHC-I and MHC-II in liver cells. While both these molecules were virtually absent in normal liver cells, MHC-I cell surface molecules were expressed at very high level in HCC cells (59). This of course was relevant to purify the MHC-I tumor peptidome and select the appropriate peptides for the vaccine compositions.…”
Section: From the Bench To The Bedside: The Construction Of An Optimamentioning
confidence: 99%
“…Importantly MHC-II expression could not be rescued even by treatment with IFNγ, the most potent inflammatory cytokine that induces MHC-II expression indirectly via the primary transcriptional activation of CIITA (19). In depth analysis of the molecular mechanism responsible of this finding demonstrated that the CIITA promoter IV, the specific promoter activated by the IFNγ (60), was silenced by hypermethylation of its sequence and thus rendered developmentally unresponsive in liver cells (59). This finding may have important effects on the interpretation of the tolerogenic environment of the liver, because the impossibility to express MHC-II molecules by liver cells, continuously in contact with massive concentrations of antigenic materials derived from the digestive tract, would prevent accidental co-participation of these cells to APC function and activation of immune system against potential food antigens as well as other antigens including self antigens.…”
Section: From the Bench To The Bedside: The Construction Of An Optimamentioning
confidence: 99%
“…17 Whereas normal hepatocytes do not express HLA class I and II, HCC cells strongly upregulate HLA class I while remaining negative for HLA class II. 18 The absence of HLA class II expression in HCC cell lines is correlated with a lack of CIITA expression. 18 This supports the hypothesis that MHC-II positive tumor cells could be recognized by the host immune system and help establish a protective immune response.…”
Section: Discussionmentioning
confidence: 99%
“…18 The absence of HLA class II expression in HCC cell lines is correlated with a lack of CIITA expression. 18 This supports the hypothesis that MHC-II positive tumor cells could be recognized by the host immune system and help establish a protective immune response. 19 Briefly, a cross-match involves placing recipient serum (potentially containing donor-specific anti-HLA antibodies) onto donor lymphocytes (containing HLAs).…”
Section: Discussionmentioning
confidence: 99%